A Study of Training Needs of Personnel in Industrial Work: A Case Study of Phra Ram 4 District, Bangkok - สาพิมพ์ เกศกนก; ถาพินนา ชัยยะเนตร; รชตวัฒนกุล รัชเมธี; พูลสวัสดิ์ ธราวุฒิ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to study the training needs of industrial personnel. The sample population was industrial personnel in the case study unit, Phra Ram 4 District, Bangkok. The sample size was set at 200 people and purposive sampling was used. The data collection tool was a 2-part questionnaire that was tested for content validity (IOC) and had a reliability of .830. The statistics used for data analysis were as follows: frequency, percentage, mean, standard deviation, and the use of statistics to compare the differences between 2 variables (Independent-Samples: t-test) and compare the differences between more than 2 variables using a one-way analysis of variance (One-way Analysis of Variance: One-way Anova: F-test). The research results in terms of personal factors found that most of the sample were male, accounting for 53 percent. The age range was 21-25 years, accounting for 51.5 percent. The education level was a bachelor’s degree, accounting for 59.5 percent. The working period was 1-3 years, accounting for 45.5 percent. The average monthly income 15,001-20,000 baht, accounting for 60.5 percent in the past year, received 1-3 work training sessions, accounting for 64.0 percent, wanted to train in an On Site format, accounting for 71.5 percent, the appropriate training period per session was half a day, accounting for 46.5 percent. Summary of training needs found that overall it was at the lowest level (1.76) and if considering each aspect, arranged from highest to lowest value, it was found that personal needs were at the lowest level (1.75), job needs were at the lowest level (1.53) and organization needs were At the lowest level (1.10) and if considering each topic in descending order, it was found that training made the participants more enthusiastic or more aware of their work (1.81), training managers should plan to continuously monitor the trainees’ work performance (1.81), you received training that continuously developed your knowledge and work skills (1.80), training content should be at an appropriate time (1.80), and the selection of training topics should be consistent with the organization’s objectives (1.79). In terms of hypothesis testing, it was found that personal factors in terms of different time periods had different training needs, and personal factors in terms of gender, age, education, work experience, average monthly income and training period, and the need for different training formats were not different.